Short Communication: Rotavirus Group A Occurrence in Rural Water Source Samples in a Midwest Region State of Brazil, Comparing Wet and Dry Seasons - Graziela Picciola Bordoni; Lucas Candido Gonçalves Barbosa; Fernando Santos Lima; Mônica de Oliveira Santos; José Daniel Gonçalves Vieira; Thais Reis Oliveira; Paulo Sérgio Scalize; Lilian Carla Carneiro (Viruses)
Identified as a potential reference pathogen by the WHO Guidelines for Drinking-Water Quality, Rotavirus (RV) is among the main enteric viruses that cause waterborne diseases. The aim of this study was to identify and correlate the presence of RV in collective and individual water sources of rural communities in the state of Goiás, within the seasons in which the collections were made (rainy and dry seasons). For this, 86 water samples in the dry period and 160 samples in the rainy period were collected. Concentration of water samples, extraction of viral genetic material and molecular tests were performed. When analyzing the presence of RV in the samples, taking into consideration the period studied, RV was found to be more prevalent in the dry season (54.7%) than in the rainy season (20%), showing a strong statistical association with the dry season (p-value < 0.001). The presence of pathogenic microorganisms in water is a public risk issue, enabling the emergence of outbreaks, endemics and epidemics. In the present research, there was an association between the presence of Rotavirus and the dry period of the year when compared to the rainy period.